Heterogeneous nuclear ribonucleoproteins in amyotrophic lateral sclerosis: what do we know?. (March 2014) - Moujalled, Diane; White, Anthony R
ABSTRACT:  Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset motor neuron disease that results from the progressive loss of motor neurons in the brainstem and spinal cord, and of upper motor neurons in the motor cortex. TDP-43 was the first protein identified in ALS. It is present in cytoplasmic inclusions in motor neurons of affected patient brains and spinal cords, a hallmark feature of this disease. Successive studies have identified missense mutations in TARDBP, and, to date, more than 40 mutations have been identified. Recent studies have indicated that altered RNA metabolism is a key feature of ALS. This article reviews an emerging role of heterogeneous nuclear ribonucleoproteins driving disease pathogenesis that include TDP-43, FUS, hnRNPA1, hnRNPA2/B1 and hnRNPA3. Determining the molecular pathways involved may provide a promising prospect for heterogeneous nuclear ribonucleoproteins being potential biomarkers in ALS in order to develop therapeutic strategies for mitigating this disease, for which there is currently no cure.